2020
DOI: 10.1039/d0nr05953f
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenic exosome-encapsulated black phosphorus nanoparticles as an effective anticancer photo-nanovaccine

Abstract: Tumor vaccines are a promising form of cancer immunotherapy, but difficulties, such as neo-antigen identification, activation of immune cells, and tumor infiltration prevent their clinical breakthrough. Interestingly, nanotechnology-based photothermal therapy...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 53 publications
0
53
0
Order By: Relevance
“…Since tumor cell derived exosomes, which carried tumor-specific antigens, could stimulate immune responses, they were explored to combine with PTT. In the study by Liu and co-workers 52 , exosomes obtained from tumor-bearing mice after PTT (hEX) were used as tumor antigens and carriers for black phosphorus quantum dots (BPQDs). In this nanoplatform (hEX@BP), hEX could protect BPQDs, the photothermal agents from rapid degradation and clearance.…”
Section: Nano-based Ptt Combined With Antigens To Induce Host Immune Responsesmentioning
confidence: 99%
“…Since tumor cell derived exosomes, which carried tumor-specific antigens, could stimulate immune responses, they were explored to combine with PTT. In the study by Liu and co-workers 52 , exosomes obtained from tumor-bearing mice after PTT (hEX) were used as tumor antigens and carriers for black phosphorus quantum dots (BPQDs). In this nanoplatform (hEX@BP), hEX could protect BPQDs, the photothermal agents from rapid degradation and clearance.…”
Section: Nano-based Ptt Combined With Antigens To Induce Host Immune Responsesmentioning
confidence: 99%
“…Recently, reports have also provided preclinical and patient data supporting positive immune modulatory effects of hyperthermia [65]. A study by Liu and colleagues [92] has shown the utility of nanotechnology-based photothermal therapy (PTT) to enhance the activity of a tumor vaccine (hEX@BP) prepared by encapsulating black phosphorus quantum dots (BPQDs) with exosomes (hEX) in the lung cancer model. Another study combined BPQDs with neoantigens in liposomes to produce a more efficacious immune response from a vaccine [15].…”
Section: Photothermal Vaccinesmentioning
confidence: 99%
“…encapsulated BPQDs with exosomes (hEX) and found that hEX@BP showed evident tumor cells inhibition in a mice subcutaneous lung cancer model. When combined with photothermal therapy, hEX@BP got a more evident inhibitory effects against tumor cells ( 41 ), demonstrating great potentials for clinical applications.…”
Section: Bioapplications Of Qds In Lungmentioning
confidence: 99%